The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4102/ojvr.v83i1.1147
|View full text |Cite
|
Sign up to set email alerts
|

Health evaluation of African penguins (<i>Spheniscus demersus</i>) in southern Africa

Abstract: The African penguin (Spheniscus demersus) is an endangered seabird that breeds along the coast of Namibia and South Africa, and disease surveillance was identified as a priority for its conservation. Aiming for the establishment of baseline data on the presence of potential pathogens in this species, a comprehensive health assessment (blood smear examination, haematology, biochemistry and serology) was conducted on samples obtained from 578 African penguins at 11 breeding colonies and a rehabilitation centre. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Blood parasites were remarkably common in African penguins examined in this study, with Babesia being the most frequent (46% prevalence on admission, 72% infection ratio), whereas Borrelia was recorded only sporadically (1% prevalence on admission, 3% infection ratio) and Plasmodium was only recorded once. Although these parasites have long been known to infect wild African penguins (Coles, 1941; Fantham and Porter, 1944), their prevalence in this study was markedly higher than in apparently wild healthy adult African penguins sampled in previous studies (Parsons et al ., 2016; Espinaze et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood parasites were remarkably common in African penguins examined in this study, with Babesia being the most frequent (46% prevalence on admission, 72% infection ratio), whereas Borrelia was recorded only sporadically (1% prevalence on admission, 3% infection ratio) and Plasmodium was only recorded once. Although these parasites have long been known to infect wild African penguins (Coles, 1941; Fantham and Porter, 1944), their prevalence in this study was markedly higher than in apparently wild healthy adult African penguins sampled in previous studies (Parsons et al ., 2016; Espinaze et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia infections are significantly associated with a decreased survival probability in African penguin chicks admitted for rehabilitation at SANCCOB (Vanstreels et al, 2019), and in some cases, Borrelia infections are lethal to penguins (Yabsley et al, 2012;Parsons et al, 2018b). Although Babesia infections have yet to be implicated in the death of African penguins, they have been linked to haematological abnormalities in otherwise apparently healthy African penguins (Parsons et al, 2016) and their potential lethality has been demonstrated in other penguin species (Parsons et al, 2017(Parsons et al, , 2018b. Furthermore, the flea P. longicornis is speculated to serve as a mechanical facilitator to the transmission of Avipoxvirus to penguins (Kane et al, 2012).…”
Section: Drown 2001mentioning
confidence: 99%
“…There are no studies conclusively demonstrating Avian orthoreovirus infection in penguins, but Gough et al (2002) isolated reovirus-like particles from the tissues of African Penguins that died with gastrointestinal and respiratory lesions at a zoo in the UK. Previous surveys of Avian orthoreovirus in penguins found seroprevalences ranging from 0% to 23% (Karesh et al 1999;Travis et al 2006;Smith et al 2008;Parsons et al 2016). In addition, antibodies to this pathogen were also reported in other seabirds that share breeding habitat with Magellanic Penguins in Patagonia (Gallo et al 2013), and it therefore seems likely that wild penguins are sporadically exposed to Avian orthoreovirus.…”
Section: Reoviridaementioning
confidence: 95%
“…Given the low positive predictive value, we would interpret our findings as potentially false positive results. In contrast, enzyme-linked immunosorbent assay (ELISA) testing of African Penguins for antibodies against this virus found seroprevalence ranging from 1% to 5% in wild populations (Parsons et al 2016). It is unclear, however, whether these serological results can be attributed to exposure to Tremovirus A or to cross-reactivity with other antigenically similar agents.…”
Section: Picornaviridaementioning
confidence: 99%
“…African penguins' vocalizations and the information they carry are important to social recognition, and ultimately the survival of their species (Favaro et al, 2015 (Parsons, Schaefer & Vanstreels, 2016;Sherley et al, 2013). The reason for this population decline is due mostly to low food availability, and breeding success that is inadequate to sustain their population (Crawford et al, 2003).…”
mentioning
confidence: 99%